2012
DOI: 10.1007/978-1-62703-131-8_29
|View full text |Cite
|
Sign up to set email alerts
|

Frog Embryo Teratogenesis Assay on Xenopus and Predictivity Compared with In Vivo Mammalian Studies

Abstract: Frog embryo teratogenesis assay on Xenopus (FETAX) has been routinely used in our laboratory for the last 12 years as a routine developmental toxicity screening test for pharmaceutical candidate compounds. To date, out of more than 400 candidates tested in FETAX, around 60 have also been evaluated in mammalian embryotoxicity studies according to standard ICH protocols.Compound teratogenic potential in both FETAX and mammalian embryotoxicity studies is determined after analysis of the developmental toxicity cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Information on involvement of neurotransmitters in pattern formation would not only identify novel components of embryogenesis, but also give important insight into potential new endpoints for teratogenic (embryotoxic) effects of widespread pharmaceuticals (Alwan et al 2007;Louik et al 2007;Colvin et al 2011;Myles et al 2013;Hurault-Delarue et al 2014;Yazdy et al 2014). To begin to identify possible patterning roles for other neurotransmitter families, this study took advantage of compounds developed for neuropharmacological research, and an exploratory drug screen was conducted in the Xenopus laevis embryo, a popular vertebrate model for the study of well-conserved developmental mechanisms (Kaltenbrun et al 2011;King et al 2012;Ori et al 2013;Pratt & Khakhalin, 2013;Schmitt et al 2014), as well as for studies of developmental toxicology (Sunderman et al 1991(Sunderman et al , 1992Fort et al 1992;Mouche et al 2011;Leconte & Mouche, 2013). This preliminary screen represents the first tier of an inverse drug screen, of the variety described by (Adams & Levin, 2006), in which drugs are tested in a hierarchical manner according to target specificity, to rapidly bypass large families with no apparent roles and progressively home in on targets with interesting functions.…”
Section: Introductionmentioning
confidence: 99%
“…Information on involvement of neurotransmitters in pattern formation would not only identify novel components of embryogenesis, but also give important insight into potential new endpoints for teratogenic (embryotoxic) effects of widespread pharmaceuticals (Alwan et al 2007;Louik et al 2007;Colvin et al 2011;Myles et al 2013;Hurault-Delarue et al 2014;Yazdy et al 2014). To begin to identify possible patterning roles for other neurotransmitter families, this study took advantage of compounds developed for neuropharmacological research, and an exploratory drug screen was conducted in the Xenopus laevis embryo, a popular vertebrate model for the study of well-conserved developmental mechanisms (Kaltenbrun et al 2011;King et al 2012;Ori et al 2013;Pratt & Khakhalin, 2013;Schmitt et al 2014), as well as for studies of developmental toxicology (Sunderman et al 1991(Sunderman et al , 1992Fort et al 1992;Mouche et al 2011;Leconte & Mouche, 2013). This preliminary screen represents the first tier of an inverse drug screen, of the variety described by (Adams & Levin, 2006), in which drugs are tested in a hierarchical manner according to target specificity, to rapidly bypass large families with no apparent roles and progressively home in on targets with interesting functions.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed methods to both screen compounds for novel phenotypes and test toxicity (Al-Yousuf et al, 2017;Tomlinson et al, 2012;Tomlinson et al, 2009;Webster et al, 2016;Liu, 2012, Saide et al, 2019). In addition, Xenopus embryos have been used as a toxicity model for drugs in their early stages of drug safety evaluation in the frog teratogenesis assay-Xenopus (or FETAX assay) (Leconte and Mouche, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Dawson and Bantle (1987) have shown that teratogenicity (determined using fish or amphibian model organisms) is strongly correlated (85%) with human malformations, and therefore should be considered as an important endpoint with wider relevance. Although, Bantle et al () suggested that a TI value >1.5 would indicate positive teratogenic potential, Leconte and Mouche () regarded TI values >1.2 as positive dysmophogenic. In the current study, exposure to Roundup (TI 1.7) and Enviro Glyphosate (TI 1.6) showed positive teratogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, exposure to Roundup (TI 1.7) and Enviro Glyphosate (TI 1.6) showed positive teratogenic potential. In terms of Leconte and Mouche (), the Kilo Max formulation with TI 1.4 could also be regarded as mildly teratogenic, given the parallel nature of the toxicity and malformation dose‐response curves of this formulation. The teratogenic potential of Roundup and Enviro Glyphosate found in this current study supports the findings of Paganelli et al (), who noted that when X. laevis were treated with glyphosate herbicide, it produced highly abnormal embryos with marked alterations in cephatic and neural crest development, and shortening of the anterior‐posterior axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation